Pengaruh Harga, Promosi dan Kualitas Produk Terhadap Pembelian Impulsif di Kota Batam - Hikmah Hikmah (Journal of Business and Economics Research (JBE), 2020)
Prices determined by the company are important in supporting consumers' decisions to make purchases. Another factor besides price that affect consumers’ choices in deciding and making purchases is promotion. Attractive promotion is able to make consumers become interested in making purchases. Product quality is a characteristic determined by the company attached to their products to win the competition in the market. The purpose of this study is to find out if the price, promotion, and product quality have any effect on the action of impulsive purchasing in Batam City. A total of 204 respondents was used as samples with a purposive sampling method in this research. Data were processed with the help of using the SPSS program version 25 with descriptive analysis and multiple linear analysis. The result of this study shows that prices do not significantly affect impulsive purchases. On the other hand, promotions and product quality significantly affect impulsive purchases. From the F test, the researcher concludes that price, promotion and product quality simultaneously affect impulsive purchases